Анатолий Папанов: снимайте шляпу, вытирайте ноги - Крылов Юрий (Питер, 2012)
Экземпляры: ф.6 (20171222) / Инвентарный номер: 2070 / Цена: / Сис.шифр: 85.37 / Авт.знак: А 64 / ГРНТИ: 18.67 / ББК: 85.374(2)